The kaleidoscopic midwife: a conceptual metaphor illustrating first-time mothers' perspectives of a good midwife: a grounded theory study - Borrelli, Sara E. (2015)
BACKGROUND The literature review reveals information about what makes a good midwife from several perspectives. However, there is a dearth of knowledge around women’s perceptions of a good midwife in different birthplaces. AIM. The aim of the study was to explore and explain first-time mothers’ expectations and experiences of a good midwife during childbirth in the context of different places of birth.